Penguatan Karakter Mandiri dan Disiplin Siswa Sekolah Dasar Melalui Implementasi Gerakan Literasi Sekolah - Arrahmi, Syukron Zahidi; Cahyani, Berliana Henu; Khosiyono, Banun Havifah Cahyo (Jurnal Didaktika Pendidikan Dasar, 2025)
Discipline and independence of students in schools is very necessary in order to support the teaching and learning process in schools to achieve the expected educational goals. One of the ways used by the school to improve student discipline and independence in literacy activities is by implementing the School Literacy Movement program in accordance with government programs. The purpose of this study was to describe the value of the disciplined and independent character of grade 3 students through the GLS at SDN Girigondo. This research aims to reveal the importance of students' discipline and independence in the School Literacy Movement program. This research uses descriptive qualitative methods, with data collection methods using observation, questionnaires and open interviews. The results of the analysis of observations, questionnaires and interviews show that not all students fulfill all the discipline and independence indicators for implementing GLS. Class 3 students received a very good category for discipline scores, but the discipline scores for the implementation of GLS for students who were superior were found in indicators of good behavior. Meanwhile, in terms of independent indicators in implementing GLS, overall students got a good category, but students were superior in indicators of responsibility in each GLS activity.